Medición de sintomas visuales en trabajadores expuestos al computador utilizando el cuestionario CVSS17 (2020)
The creation of computers has changed the lives of many generations, and has transformed the workplace. “With the invention of computers, all work obligations can be completed in a single device, becoming an important part of everyday life. The constant use of these devices has made users to experience the symptoms of Computer Vision Syndrome (CVS) (1). "CVS can have a significant impact, not only on visual comfort but also on productivity at work. Thus, between 64% and 90% of computer users experience symptoms like eyestrain, headaches, dry eye disease, diplopia and blurred vision, it happens at looking at near or far distance, or even after prolonged computer use” (2). This study presents a quantitative type approach, with a cross-sectional design, the class of study is observational, descriptive, survey type, the analysis will be addressed through a univariate statistical approach and variable crossing. Otherwise, the population was made up of 49 workers from a company, while the selected sample was 41 workers. Finally, to carry out the study, it was used the CVSS17 scale validated in Spanish, which can determinate the presence of 17 symptoms in workers affected by the use of computer screens for long days. Obtaining, as a result, the most common symptom is eye fatigue with 71%, followed by dry eye with 44%, and heaviness of the eyelids for 36%. It is recommended to carry out more studies on this topic due to population growth and, likewise, new jobs that involve excessive use of computers, generating multiple visual symptoms.